2010
DOI: 10.5012/bkcs.2010.31.11.3272
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Peripherally Ferrocene-modified Zinc Phthalocyanine for Dye-sensitized Solar Cell

Abstract: Synthesis and structural characterization of peripherally ferrocene-substituted zinc phthalocyanine (ZnPc-Fc) were carried out for efficient far-red/near-IR performance in dye-sensitized nanostructured TiO2 solar cells. Incorporating ferrocene into phthalocyanine strongly improved the dye solubility in polar organic solvents, and reduced surface aggregation due to the steric effect of bulky ferrocene substituents. The involvement of electron transfer reaction pathways between ferrocene and phthalocyanine in Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The preparation of highly efficient functional materials for solar energy conversion is of fundamental interest. Because of their outstanding absorption properties, numerous porphyrinoids coupled with organic or organometallic donor fragment(s) have been investigated in dye-sensitized solar cells and organic photovoltaics. The photophysical properties of ferrocenylporphyrins, phthalocyanines, tetraazaporphyrins, and subphthalocyanines have recently been investigated by several research groups, and the ferrocene (Fc)-based substituents were found to be prominent electron-donating groups. BODIPYs and aza-BODIPYs (where BODIPY = dipyrrometheneboron difluoride) have recently emerged in this field because of their unique photophysical properties. Several Fc-containing BODIPY conjugates with a Fc group linked via a spacer located at the α- or β-pyrrolic or meso position have been reported. However, to the best of our knowledge, no reports are available on BODIPYs and aza-BODIPYs with Fc substituents connected via the central boron atom using direct organometallic B–C bonds. Bonding the Fc ligands at the boron atom leaves them in close proximity to aza-BODIPY but without conjugated through-bond coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of highly efficient functional materials for solar energy conversion is of fundamental interest. Because of their outstanding absorption properties, numerous porphyrinoids coupled with organic or organometallic donor fragment(s) have been investigated in dye-sensitized solar cells and organic photovoltaics. The photophysical properties of ferrocenylporphyrins, phthalocyanines, tetraazaporphyrins, and subphthalocyanines have recently been investigated by several research groups, and the ferrocene (Fc)-based substituents were found to be prominent electron-donating groups. BODIPYs and aza-BODIPYs (where BODIPY = dipyrrometheneboron difluoride) have recently emerged in this field because of their unique photophysical properties. Several Fc-containing BODIPY conjugates with a Fc group linked via a spacer located at the α- or β-pyrrolic or meso position have been reported. However, to the best of our knowledge, no reports are available on BODIPYs and aza-BODIPYs with Fc substituents connected via the central boron atom using direct organometallic B–C bonds. Bonding the Fc ligands at the boron atom leaves them in close proximity to aza-BODIPY but without conjugated through-bond coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The redox couple electrolyte subsequently reduces the dye molecule to its ground state while the electrolyte is regenerated at the counter electrode, resulting in open circuit voltage ( V OC ) and short circuit current ( J SC ). Recently, Daeneke et al reported a DSSC study using ferrocenyl derivatives as redox electrolytes to understand the variation of dye regeneration efficiency with the change in ferrocene/ferrocenium redox potential . This and a handful of other reports showed that ferrocenyl compounds are mostly used as redox couples and have never been used as effective sensitizers in DSSC due to their comparatively larger band gap that can only absorb a very small part of the solar spectrum .…”
mentioning
confidence: 99%
“…Recently, Daeneke et al reported a DSSC study using ferrocenyl derivatives as redox electrolytes to understand the variation of dye regeneration efficiency with the change in ferrocene/ferrocenium redox potential . This and a handful of other reports showed that ferrocenyl compounds are mostly used as redox couples and have never been used as effective sensitizers in DSSC due to their comparatively larger band gap that can only absorb a very small part of the solar spectrum . Thus, designing a ferrocenyl derivative that can absorb a significant part of visible light that could not only act as a photon absorber but also, because of its intrinsic redox properties, would be able to regenerate the dye after the photogenerated electron has been transferred to the TiO 2 layer would obviate any additional redox electrolyte in the solar cell device.…”
mentioning
confidence: 99%
“…It should be noted that most previous protocols for the syntheses of the diesters 2 Et and 2 Me involved esterification of fc(COOH) 2 ( 4 ), ,, while here the opposite approach was pursued, with the ester 2 Et serving as a precursor for the preparation of 4 . Hence, saponification of the diester 2 Et on scales up to 150 g was performed at elevated temperature by addition of aqueous NaOH solution to an ethanol solution of 2 Et , producing the sodium salt fc(COONa) 2 , which was isolated by filtration, dissolved in water, and protonated by addition of concentrated HCl.…”
Section: Resultsmentioning
confidence: 99%